2020
DOI: 10.1093/rheumatology/keaa105
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia in primary Sjögren’s syndrome is associated with premature aging of naïve CD4+ T cells

Abstract: Objective To investigate peripheral lymphopenia, a frequent finding in primary Sjögren’s syndrome (pSS) associated with higher disease activity and increased mortality. Methods Prospective, cross-sectional study of consecutive patients with pSS (n = 66) and healthy controls (n = 181). Lymphocyte subsets were analysed by flow cytometry, naïve (CD45RA+) and memory (CD45RO+) CD4+ T cells were purified by MACS technology. In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This phenomenon indicates that a common mechanism presented as lymphopenia may exist for the induction of autoimmunity. Of note, markers of immune aging have been documented in the ADs in humans [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ] ( Table 1 ), such as reduced percentage of TREC + cells and/or lymphopenia, LIP in T cell subsets, and loss of CD28 + cells/accumulation of CD28 null cells in T cell subsets ( Table 1 ).…”
Section: Lymphopenia In Physiological and Autoimmune Conditionsmentioning
confidence: 99%
“…This phenomenon indicates that a common mechanism presented as lymphopenia may exist for the induction of autoimmunity. Of note, markers of immune aging have been documented in the ADs in humans [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ] ( Table 1 ), such as reduced percentage of TREC + cells and/or lymphopenia, LIP in T cell subsets, and loss of CD28 + cells/accumulation of CD28 null cells in T cell subsets ( Table 1 ).…”
Section: Lymphopenia In Physiological and Autoimmune Conditionsmentioning
confidence: 99%
“…T cells comprise the helper T cell populations (CD4+), which differentiate in several subsets such as Th1, Th2, Th17, regulatory T cells (Treg), and T follicular helper cells (Tfh), as well as CD8+ T cells, also called Cytotoxic T Lymphocytes (CTL) [ 4 ]. Increased T cells infiltration into salivary glands (SG) from pSS patients has been evidenced accomplished by decreased levels in periphery blood, supporting the hypothesis that lymphopenia, a frequent finding in pSS patients associated with higher disease activity and increased mortality, might be owed to T cells migration [ 5 ].…”
Section: Introductionmentioning
confidence: 95%
“…Vitali et al found that IFNG, TRIM26 , and EDN1 were overexpressed in pSS patients ( 12 ). Although studies have linked pSS to the immune system response in vivo ( 13 , 14 ), there is a lack of novel immune-related genes to study the underlying causes and inform treatment.…”
Section: Introductionmentioning
confidence: 99%